Association between dietary index for gut microbiota and metabolic syndrome risk: a cross-sectional analysis of NHANES 2007–2018 - Yueyue Niu; Lu Xiao; Ling Feng (Scientific Reports)
Abstract Metabolic syndrome (MetS) poses a significant global health challenge, closely associated with cardiovascular diseases, diabetes, and other conditions. With the global prevalence of MetS steadily rising, the potential role of gut microbiota in its development has garnered increasing attention. Against this backdrop, the present study aims to explore the association between the dietary index for gut microbiota (DI-GM) score and MetS. This cross-sectional study utilized data from the 2007–2018 U.S. National Health and Nutrition Examination Survey (NHANES), including 339,242 adults aged ≥ 18 years. The DI-GM score, constructed based on 14 food or nutrient components, served as the exposure variable. MetS was defined according to the Adult Treatment Panel III (ATP III) criteria, including abdominal obesity (waist circumference ≥ 102 cm in men and ≥ 88 cm in women), elevated triglycerides (≥ 150 mg/dL), reduced HDL cholesterol (< 40 mg/dL in men and < 50 mg/dL in women), elevated blood pressure (≥ 130/85 mmHg), and elevated fasting glucose (≥ 100 mg/dL). Multivariable logistic regression analyses were performed to adjust for demographic characteristics, lifestyle factors, and other potential confounders. Higher DI-GM scores were significantly associated with a reduced risk of MetS. After adjusting for all confounders, individuals in the highest quartile (Q4) of DI-GM scores had a 16% lower risk of MetS compared to those in the lowest quartile (Q1) (OR: 0.84; 95%CI: 0.70–1.01). Mediation analyses revealed that systemic immune-inflammation index (SII) and neutrophil-to-lymphocyte ratio (NLR) mediated 4.63% and 3.83% of the association between DI-GM and MetS, respectively. There is an inverse association between DI-GM scores and the risk of MetS, potentially mediated in part by inflammatory markers. These findings provide new evidence supporting dietary interventions aimed at improving gut microbiota to prevent MetS.